Curriculum-based Ideological and Political Education in Comprehensive English Courses Under the Background of New Liberal Arts - Cui, Shaofang (Pacific International Journal, 2025)
Against the backdrop of the “New Liberal Arts” initiative, which emphasizes interdisciplinary integration, value orientation, and social responsiveness, higher foreign language education is required to transcend the traditional focus on linguistic skills and integrate ideological and political guidance into teaching practice. This study explores the implementation path and effectiveness of Curriculum-based Ideological and Political Education (CIPE) in Comprehensive English courses, a core course for non-English majors in Chinese universities. Adopting an action research approach, the study was conducted with 86 first-year non-English major students (divided into an experimental group and a control group) from a university in eastern China over a 16-week semester. Research tools included teaching design schemes (with CIPE elements integrated for the experimental group), pre/post-language proficiency tests, pre/post-ideological cognition questionnaires, and semi-structured interviews with students and teachers. Quantitative data were analyzed using SPSS 26.0, while qualitative data were coded via Nvivo 12.0. Results showed that: 1) The experimental group outperformed the control group in both language proficiency (e.g., reading comprehension, writing coherence) and ideological literacy (e.g., cultural confidence, social responsibility); 2) Students in the experimental group demonstrated higher recognition of the integration of CIPE into English teaching, reporting enhanced interest in cross-cultural communication and a deeper understanding of Chinese values; 3) Teachers involved in the study reported improved ability to identify and integrate ideological elements into textbook content. The findings confirm that integrating CIPE into Comprehensive English courses under the New Liberal Arts framework can achieve the "dual goals" of linguistic competence cultivation and value guidance, providing empirical support for the reform of foreign language education in the New Liberal Arts era.